Hemorrhagic, thrombotic and obstetric complications of congenital dysfibrinogenemia in a previously asymptomatic woman. Issue 196 (December 2020) - Peterson, Wynn; Liederman, Zachary; Baker, Jillian; Floros, Georgina; Martin, Rachel; Berger, Howard; Meffe, Filomena; Teitel, Jerry; Sholzberg, Michelle
Highlights: Dysfibrinogenemia is a highly heterogeneous disorder. Clinical manifestations can vary across successive pregnancies. In vitro fibrinogen activity at delivery is weakly correlated with clinical outcomes. Fibrinogen replacement may fail to improve in vitro fibrinogen activity. An individualized approach to management of dysfibrinogenemia in pregnancy is required.